2012
DOI: 10.1007/s12262-012-0760-9
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Redo-Laparotomies: Patterns and Outcome—A Single Centre Experience

Abstract: A proportion of the operations performed in a surgical gastroenterology department are unplanned repeat laparotomies for complications of the original procedure. We examined why, in our department, these 'redo' laparotomies were performed and what was their outcome. We retrospectively analyzed 6530 patients operated between September 1996 - December 2010, of these 257 redo laparotomies were performed in 193(2.5 %) patients. There were 138 males and 55 females who had a mean age of 42 years (range 7-68 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 8 publications
7
31
2
Order By: Relevance
“…In a study evaluating UARLs, the mortality rate was found to be 33% (2). It was reported to be 37.03% in the study of Unalp et al (1). In our study, the mortality rate was 27%.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In a study evaluating UARLs, the mortality rate was found to be 33% (2). It was reported to be 37.03% in the study of Unalp et al (1). In our study, the mortality rate was 27%.…”
Section: Discussionsupporting
confidence: 52%
“…UARLs are still the most important step of the treatment for these patients (1,3). The mortality rates vary between 50 and 100% in cases with peritonitis that cannot be taken under control, namely those with spesis and multiple system organ failure (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Majority of relaparotomy were performed due to leak from anastomotic site in all the studies. [1][2][3][4] Mean duration between first laparotomy and relaparotomy was 6.85 days in our study. One of the study had mean duration between two laparotomies to be 5 days, while another had mean duration to be 6.95 days.…”
Section: Discussionmentioning
confidence: 92%
“…Some of the important indications of relaparotomy are anastomotic leakage, septic peritonitis, intestinal obstruction, burst abdomen, intestinal perforation and haemorrhage. [1][2][3] Measures which can be carried out to reduce the incidence of relaparotomy are proper pre-operative work up, use of newer anaesthetic techniques, newer antibiotics and proper antiseptics, better post-operative fluid and electrolyte balance, proper Incidence of relaparotomy can be decreased by proper understanding of predisposing factors and by taking appropriate measures. Emergency, sepsis, primary suppurating disease, these are some factors, because of which incidence of relaparotomy cannot be brought down further.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation